Poetry, destruction, reconstruction: Trilce XXXVI, César Vallejo’s first ars politica? - Fortunato Brakspear, Owen (2023)
Via a rereading of the poem «XXXVI» by César Vallejo, this article explores the connections between this earlier poem, and Vallejo’s later poetry. The most prominent theme in this relation is the presence in each of the poems under discussion, of the process of redistribution. Indeed, this process is not only mentioned or implicated by the poems on a semiotic and metaphoric level; redistribution is imbricated in the language and axiology of the poems, at the fundamental level of their linguistic and grammatical formation. This article examines how this process, nascent and more metaphysical in «XXXVI», becomes an integral element of the poetic socialism of Vallejo’s final poems, those which present, most explicitly and powerfully, his radical vision.